2019
DOI: 10.1111/1475-6773.13220
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination in the United States: Experiences of black Americans

Abstract: Objective To examine experiences of racial discrimination among black adults in the United States, which broadly contribute to their poor health outcomes. Data Source and Study Design Data come from a nationally representative, probability‐based telephone survey including 802 non‐Hispanic black and a comparison group of 902 non‐Hispanic white US adults, conducted January–April 2017. Methods We calculated the percent of blacks reporting discrimination in several domains, including health care. We used logistic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
82
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 190 publications
(86 citation statements)
references
References 36 publications
4
82
0
Order By: Relevance
“…Black, Hispanic, Asian American, and Native American adults are more likely to report experiencing discrimination in health care and avoiding health care out of concern for discrimination or poor treatment compared to white adults [ 14 , 15 , 16 , 17 ]. Patients’ acceptance of home health care is associated with the quality of hospital discharge planning communication and prior positive or negative experiences with post-acute care [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Black, Hispanic, Asian American, and Native American adults are more likely to report experiencing discrimination in health care and avoiding health care out of concern for discrimination or poor treatment compared to white adults [ 14 , 15 , 16 , 17 ]. Patients’ acceptance of home health care is associated with the quality of hospital discharge planning communication and prior positive or negative experiences with post-acute care [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, over the last several years, a constant and growing barrage of national news reports have illuminated the PLOS ONE myriad occurrences of racial discrimination experienced by African American women, men, and children across the country. White bystanders have requested unnecessary police intervention in situations where African Americans are engaging in routine, everyday activities such as bird watching, jogging, swimming in community pools, operating lemonade stands, entering their apartments, moving into new single-family homes, hosting neighborhood barbeques, or transacting business with their bank teller at a local financial institution [12,[23][24][25][26][27][28][29][30][31][32][33][34][35][36]. Paralleling these news reports is an uptick in anti-Black hate crimes documented by the Federal Bureau of Investigation across 2017 and 2018 [24,25].…”
Section: Sociodemographic Variations In Exposure To Dimensions Of Discriminationmentioning
confidence: 99%
“…Across decades of social science research, African Americans consistently self-report the highest levels of race-related and general interpersonal discrimination across major life domains. Indeed, 80 to 100% of African Americans report lifetime exposure to racial discrimination in daily life [26][27][28][29][30][31][32]. In one longitudinal study, 90% of African Americans reported persistent racial discrimination at work; in the marketplace; when seeking employment, housing, or medical care; and when engaging with law enforcement and the judicial system across a seven-year span [40].…”
Section: Characterizing Discrimination In Blacksmentioning
confidence: 99%
“…Difficulty affording medications leads patients to make unpalatable decisions, such as taking medications less frequently than prescribed, buying less nutritious food to afford medication, or choosing between the needs of family members or their own needs. 35 Furthermore, people with low income are subject to structural forces that suppress wages, create dangerous work environments, undermine social services, limit affordable and stable housing, create food deserts, contribute to disproportionate rates of incarceration or control by judicial systems, threaten the social fabric of early childhood, make health care less accessible, expose people to pollutants, undercut the quality of primary and secondary education, and limit access to higher education, thereby maintaining a skewed playing field. 9 As described above, the poor are blamed for their poverty.…”
Section: Recommendations and Pathwaysmentioning
confidence: 99%